Improving Clinical Reasoning Skills Through Educational Approaches in Pharmacy Students: Literature Review - Sri Rahmawati; Aliefman Hakim; Agus Abhi Purwoko; Agus Ramdani; AA Sukarso (Postgraduate Program, University of Mataram, 2025)
This study aims to review the literature on the development of Clinical Reasoning Skills (CRS) in pharmacy students, with a focus on educational approaches that enhance essential competencies in effective patient care. Using the PRISMA methodology, a systematic search was conducted in the SCOPUS database, yielding 3,794 documents. Screening based on relevance, publication date, and language narrowed the number to 1,140 documents, which were further screened for eligibility, yielding 34 documents, of which 12 met inclusion criteria for in-depth analysis. The results showed that structured and multifaceted pedagogical methods, such as cognitive apprenticeship, team-based learning, and experiential learning in real-world settings, were effective in enhancing CRS in pharmacy students. These approaches strengthen critical thinking, problem-solving, and collaboration skills, which are essential in dealing with the complexity of patient care scenarios. In addition, the use of innovative assessment tools, such as script concordance tests, allows for reliable measurement of reasoning skills and provides targeted feedback, thereby enhancing student readiness for clinical practice. The review concludes that the integration of these learning methods into the pharmacy curriculum contributes to the development of student competencies and prepares graduates for interdisciplinary collaboration. Future research is needed to explore the long-term effectiveness of this educational strategy across contexts and examine the use of technology, such as virtual simulation, to further optimize CRS training and ensure pharmacy graduates are prepared to meet evolving health care challenges.